The Prediction of Self-care Behaviors and Quality of Life Based on Disease Perception in Patients with Heart Failure - M Eydi; T Najafi Ghezeljeh; SH Haghani (Iran University of Medical Sciences, 2020)
Background & Aims: Heart failure (HF) is a disorder that is caused by the inability of the heart to pump blood properly due to the disorders in the structure or function of the heart. Quality of life (QOL) is lower in patients with HF compared to the general population and patients with other chronic diseases. For optimal QOL, it is necessary to change behaviors and follow treatment regimens throughout the period of self-care. The impact of any chronic and long-term condition on the patients and their ability to optimize self-care could be attributed to several factors, such as the understanding of the condition and its nature, impact of the condition on the ability of the patient to perform daily activities, beliefs and expectations, patientchr('39')s involvement in self-care, and support. Disease perception could affect the mental health of the patients and management of the disease, thereby affecting their self-care behaviors and QOL. The present study aimed to predict the self-care behaviors and QOL based on the disease perception of patients with HF. Materials & Methods: This cross-sectional was conducted with a predictive correlational design during January 2017-May 2016 on 150 patients with HF, who were selected via continuous sampling based on the inclusion criteria of the confirmed diagnosis of HF by a physician and a minimum of six months past the disease, age of more than 18 years, and ability to communicate and literacy to complete the questionnaires. Data were collected in a self-report manner using the European HF self-care behavior scale, a brief illness perception questionnaire, and Minnesota living with heart failure questionnaires. The European HF self-care behavior scale consists of 12 items, and the responses are scored based on a five-point Likert scale (Completely=1, Not at All=5) within the score range of 12-60. The lower scores in this questionnaire show the better self-care behavior of individuals and vice versa. The brief illness perception questionnaire has eight items, which were prepared based on the modified version of the questionnaire. The items are scored within the range of 0-10, and the score obtained from the eight items is within the range of 0-80, which is the highest score indicating the patientchr('39')s understanding of the high risk of the disease. The Minnesota living with heart failure questionnaires has 21 items that are scored based on a six-point Likert scale (0-5), and the total score is within the range of 0-105, and the higher scores show the lower QOL of the patient. Data analysis was performed in SPSS version 16 using Pearsonchr('39')s correlation-coefficient, the analysis of variance (ANOVA), Chi-square, independent t-test, and regression analysis. Results: The mean score of the illness perception was 59.42±7.86, the mean score of self-care behaviors was 36.24±7.79 (moderate), and the mean score of QOL was 59.53±16.84 (poor). A significant, direct, and weak correlation was observed between the illness perception and self-care behaviors (P<0.001; r=0.26). In addition, self-care was the only predictor of illness perception, and illness perception and QOL had a direct, significant correlation (r=0.48; P<0.001). The results of multiple linear regression analysis showed that illness perception, adequate income, education level, number of hospitalizations, and classification of HF were the predictors of QOL. The mean score of the illness perception was 59.42±7.86, and the mean score of self-care behaviors was 36.24±7.79 (maximum: 53, minimum: 15), which indicated the moderate self-care of the patients. The minimum and maximum scores of QOL were zero and 97, respectively with the mean score of 59.53±16.84, which indicated the poor QOL of the research units. A weak, significant correlation was observed between the illness perception and self-care of the patients (r=0.26; P<0.001), so that with the increased score of illness perception, the self-care scores of the patients increased. In the results of the multiple linear regression analysis indicated that the only self-care could predict self-care (P=0.046), so that with the increased score of illness perception by one point, the self-care scores of the patients increased by 0.15 units. Therefore, when the patient is threatened to perceive their disease, their self-care becomes weaker (Table 2). In addition, the correlation between the two variables of illness perception and QOL was direct and significant (P<0.001; r=0.48). As the scores of disease perception increased, the QOL of the patients was higher, so that the more the patient perceives the threat of the disease, the poorer their QOL becomes. The results of multiple linear regression analysis indicated that per one unit of increase in the perception of the disease, the QOL score increased by 0.33, which shows the deterioration of the QOL. The QOL in those with sufficient income was lower by 0.14 compared to those with insufficient income. Furthermore, the QOL score of those with an undergraduate degree (below diploma) was lower by 0.22 compared to those with higher education. The patients without the history of hospitalization had higher QOL scores by 0.31 compared to those with 5-10 hospitalizations, indicating the better QOL. In addition, the QOL score of the patients with HF class II was lower by 0.29 units and 0.16 units in those with HF class III compared to those with HF class IV, which indicated their better QOL. Conclusion: According to the results, illness perception predicts QOL and self-care behaviors. In this study, patients with HF, which is a common chronic disease, were examined. In these patients, the perception and cognition that a person is affected by other factors of his disease affects the perception of their physical needs, followed by their activities and the behaviors that influence self-care and meeting needs. However, it should be noted that in addition to illness perception, other factors play a key role in the self-care of patients with HF, which must be investigated in the future studies. The healthcare professionals (especially nurses) who are more in contact with patients could improve the patientschr('39') perceptions through education to increase their self-care and QOL. The patients with poor illness perception had more negative self-care behaviors. The healthcare professionals (especially nurses) who are more in contact with patients could improve the patientschr('39') perceptions through education to increase their self-care. The results showed that poor illness perception was associated with the lower QOL. Therefore, it is suggested that interventions such as counseling and follow-up programs be considered to improve the understanding of diseases, so that QOL could be enhanced. Research must be focused on the effectiveness of these interventions. Considering the association between illness perception and self-care behaviors in the HF patients and the predictive role of disease perception (especially for QOL), nursing managers could provide facilities for planning and implementing the necessary measures to improve the patientchr('39')s understanding of HF upon admission and referral to medical centers or the proper conditions should be provided for the implementation of counseling and follow-up sessions in the management of the patients at home.